1985
DOI: 10.1037/0033-2909.98.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for treatment: A review with special emphasis on alcoholism.

Abstract: Motivation is often regarded as a client attribute related to maladaptive defense mechanisms, and it is used to explain unfavorable treatment outcome. This article provides an integrative review of research relating motivational variables and interventions to treatment entry, compliance, and outcome; special focus is on alcoholism and other addictive behaviors. Empirical evidence is considered regarding motivational interventions including advice, feedback, goal setting, role playing, modeling, contingencies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
287
1
19

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(319 citation statements)
references
References 219 publications
(341 reference statements)
12
287
1
19
Order By: Relevance
“…Three of the more commonly used measures in this regard are the Readiness Ruler, staging (stage of change) algorithm, and the Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES). The Readiness Ruler (Miller, 1985(Miller, , 1999 represents a 1-10 continuum of "readiness to change," with the anchor points not ready to change to unsure to ready to change to trying to change. A similar measure, the Marijuana Ladder, consists of a diagram of a ladder with 10 "rungs," several of which are anchored by verbal labels of different degrees of readiness to change.…”
mentioning
confidence: 99%
“…Three of the more commonly used measures in this regard are the Readiness Ruler, staging (stage of change) algorithm, and the Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES). The Readiness Ruler (Miller, 1985(Miller, , 1999 represents a 1-10 continuum of "readiness to change," with the anchor points not ready to change to unsure to ready to change to trying to change. A similar measure, the Marijuana Ladder, consists of a diagram of a ladder with 10 "rungs," several of which are anchored by verbal labels of different degrees of readiness to change.…”
mentioning
confidence: 99%
“…Self-stigma: Building on Scheff (1966)'s discussion of individuals' internalization of cultural stereotypes of mental illness, Link (1987) summarized two negative consequences that might arise through individuals' association with mental health institutions, premised upon the largely negative images of mental illness and mental services in Western culture and beyond: First, individuals may devalue themselves since they are now officially falling into an institutional category that is negatively viewed by the public, and second, individuals may develop defensive or other negative social actions and interactions due to internalized concerns of how others may think of them. As for the former, studies have shown that in fear of losing self-esteem, self-efficacy, or self-autonomy, individuals might choose not to seek professional assistance despite the fact that they are suffering mental distress (Miller 1985;Nadler 1986a, b;Vogel et al 2006). As for the latter, individuals might avoid services or even rearrange their lives because of feelings of shame, embarrassment, or guilt that could be invoked by fear that others would find out that they are receiving services .…”
Section: Beliefs and Expectations About The Efficacy Of Professional mentioning
confidence: 99%
“…may reinforce the client's view that relationships are inevitably grounded in coercion and control, rather than in understanding, trust, and support" (p. 609). Empirical literature with other populations and other treatment modalities concludes that, in addition to being ineffective, confrontational approaches frequently lead to other negative outcomes (Gurman & Kniskern, 1978;Lambert & Bergin, 1994;Miller, 1985). Given that the risk for a negative outcome appears to be especially relevant to those of very low self-esteem and lower social status (Kaplan, 1982;Lambert & Bergin, 1994), abusers may be particularly unresponsive or even at risk for deterioration in the face of unbridled or harsh confrontation.…”
Section: Difficulty Of Engaging the Resistant Batterermentioning
confidence: 99%
“…One reason is that standard treatment formats fail in their efforts to engage resistant batterers, who normally comprise most court-ordered offenders. For example, the typical stance of the Duluth model is to confront the batterer's denial, although confrontational approaches with other resistant populations (such as substance abusers) have been proven to lead to negative outcomes (Lambert & Bergin, 1994;Miller, 1985). Moreover, the use of skills-training and other behavioral techniques in cognitive-behavioral approaches assumes a well-motivated client (Daniels & Murphy, 1997).…”
Section: Introductionmentioning
confidence: 99%